Correlation between Parental Vaccine Hesitancy, Sociodemographic Factors, and Novel SARS-CoV-2 Vaccination P R Health Sci J 2022;41(4):185-191/Reply - Sookaromdee, Pathum; Wiwanitkit, Viroj; Colon-Diaz, Maricarmen (Puerto Rico Health Sciences Journal, 2023)
n/a